Asymmetric exchange rate pass-through in turkish imports of cocoa beans - Nazif Durmaz; John Kagochi (Journal of Risk and Financial Management, 2022)
The present paper uses asymmetric cointegration and error-correction modeling where a nonlinear adjustment of the exchange rate yields results that are different than those yielded by linear models. We study cocoa imports for Turkey with advanced ARDL and nonlinear ARDL frameworks. Our findings reveal that there is considerable asymmetry for the case of Turkish cocoa bean imports from Côte d'Ivoire. Compared with imports from Ghana, there are significant differences in Turkish importers' preferences when choosing between the two cocoa bean providers. Our results provide support for the nonlinear adjustment of the real Turkish lira-US dollar exchange rate and a hint of imperfect rivalry in Turkish cocoa bean imports.
Keywords: 650; asymmetric cointegration; exchange rate pass-through; nonlinear ARDL; Turkish cocoa imports